2019
DOI: 10.1038/s41598-019-44692-4
|View full text |Cite
|
Sign up to set email alerts
|

Remote Tracking of Phase Changes in Cr2AlC Thin Films by In-situ Resistivity Measurements

Abstract: Resistivity changes of magnetron sputtered, amorphous Cr 2 AlC thin films were measured during heating in vacuum. Based on correlative X-ray diffraction, in-situ and ex-situ selected area electron diffraction measurements and differential scanning calorimetry data from literature it is evident that the resistivity changes at 552 ± 4 and 585 ± 13 °C indicate the phase transitions from amorphous to a hexagonal disordered solid solution structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 35 publications
5
22
1
Order By: Relevance
“…XRD measurements (shown in Figure 1b) at room temperature show that the coating is amorphous while reflections from the Al 2 O 3 substrate are visible, indicating that the substrate temperature of 255 C during deposition is too low to activate any crystallization processes in the coating. This is in agreement with previous investigations by Stelzer et al, [37] suggesting that a postheat treatment after deposition is necessary for the formation of the desired hexagonal Cr 2 AlC MAX-phase when deposited within this temperature range.…”
Section: Characterization Of the Magnetron-sputtered Cr-al-c Coatingsupporting
confidence: 93%
“…XRD measurements (shown in Figure 1b) at room temperature show that the coating is amorphous while reflections from the Al 2 O 3 substrate are visible, indicating that the substrate temperature of 255 C during deposition is too low to activate any crystallization processes in the coating. This is in agreement with previous investigations by Stelzer et al, [37] suggesting that a postheat treatment after deposition is necessary for the formation of the desired hexagonal Cr 2 AlC MAX-phase when deposited within this temperature range.…”
Section: Characterization Of the Magnetron-sputtered Cr-al-c Coatingsupporting
confidence: 93%
“…Recently, changes in electrical resistance have been correlated to phase changes in Cr 2 AlC,19 while pioneering work by Rauh et al20 and Case21 conducted in the 1990s and 1980s showed that electrical resistance measurements are useful to study the initial stage of oxidation of 50–60 nm thick Cu20 and of 45 nm thick V21 films. In contrast to these sub‐100 nm investigations on metals, results of in situ measured sheet resistances will be employed to track the remaining film thickness of the approx.…”
Section: Resultsmentioning
confidence: 99%
“…This low temperature growth strategy resulted in the formation of X-ray amorphous coatings which were subsequently annealed at 600°C in a vacuum furnace evacuated to 0.15 mPa. According to Stelzer et al [15] this results in the formation of Cr 2 AlC MAX phase. Further deposition methodology related details can be found in [15].…”
Section: Experimental Details and Methodsmentioning
confidence: 96%
“…According to Stelzer et al [15] this results in the formation of Cr 2 AlC MAX phase. Further deposition methodology related details can be found in [15]. Energy dispersive X-ray spectroscopy (EDX) data were acquired using an Oxford system within FEI Quanta 250F scanning electron microscope at an acceleration voltage of 12 kV.…”
Section: Experimental Details and Methodsmentioning
confidence: 96%